Preferences of different tick species for human hosts in Turkey - GARGILI KELEŞ, AYŞEN (SPRINGER, 2013)
The ticks removed from the patients who applied to the hospitals in Istanbul and neighboring cities, Turkey, with the complaint of tick bite were examined in this study, on account of their species, biological stages, attachment sites on the body, and the age of the affected patients. A total of 16,969 ticks were identified. Encountered species were as follows: 33.6 % Ixodes spp. immature, 25.3 % Hyalomma spp. immature, 24.3 % I. ricinus, 9.5 % Rhipicephalus sanguineus gr., 3.2 % R. bursa, 2.2 % Hyalomma marginatum, 1.96 % Haemaphysalis adults, 1.66 % Hyalomma aegyptium, 0.52 % Dermacentor marginatus, 0.39 % Rhipicephalus spp. nymphs, 0.12 % Dermacentor spp. nymphs, 0.11 % Haemaphysalis spp. nymphs, 0.09 % Hyalomma scupense, and 0.03 % Hyalomma excavatum. The distribution of attachment sites of the species and instars showed significant differences. Furthermore, age data of the patients also revealed that certain tick species were more common within certain age groups.
Keywords: Tick; Human; Body site; Host age; BORRELIA-BURGDORFERI; IXODES-SCAPULARIS; LYME-DISEASE; ATTACHMENT; TRANSMISSION; DURATION; ACARI; LYMPHADENOPATHY; IXODIDAE; SITES